2022
DOI: 10.1155/2022/1269747
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Alleviates Sepsis-Induced Liver Injury by Inhibiting Hepatocyte Pyroptosis via Inhibition of the ROS/TXNIP/NLRP3 Signaling Pathway

Abstract: Sepsis is a systemic inflammatory response syndrome caused by a dysregulated host response to infection. Peroxisome proliferator-activated receptor gamma (PPARγ) exerts anti-inflammatory and antioxidative properties. To investigate the potential effects of PPARγ on sepsis-induced liver injury and determine the related mechanisms, C57BL/6 male mice were subjected to cecal ligation and puncture (CLP) to create a sepsis model which was treated with GW1929 or GW9662 to upregulate or downregulate the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…At the same time, TXNIP can directly bind to NLRP3 and activate the NLRP3 inflammasome, further aggravating oxidative stress [22]. Previous studies have also demonstrated that the regulation of NLRP3 by TXNIP is dependent on ROS [47,48]. In this study, it was found that the decrease and increase of TXNIP correspond to the decrease and increase of oxidative stress, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…At the same time, TXNIP can directly bind to NLRP3 and activate the NLRP3 inflammasome, further aggravating oxidative stress [22]. Previous studies have also demonstrated that the regulation of NLRP3 by TXNIP is dependent on ROS [47,48]. In this study, it was found that the decrease and increase of TXNIP correspond to the decrease and increase of oxidative stress, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…Bacteroides species gathered in Cluster 3 and interacted with a few genes from Cluster B outstandingly. Among these gene interactions, Mmp9, a well-studied metalloprotease involved in barrier disruption, was positively correlated with Bacteroides species, while Cth, which encodes cystathionine-γ-lyase, a major endogenous hydrogen sulfide-producing enzyme shown to suppress inflammation through IL-8 signaling [ 22 , 23 ], was negatively correlated. Correlation analysis of the ileum also revealed three main bacterial clusters and three gene clusters (Additional file 6 : Figure S4C).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, TXNIP can directly bind to NLRP3 and activate the NLRP3 inflammasome, further aggravating oxidative stress [ 22 ]. Previous studies have also demonstrated that the regulation of NLRP3 by TXNIP is dependent on ROS [ 47 , 48 ]. In this study, it was found that the decrease and increase of TXNIP correspond to the decrease and increase of oxidative stress, respectively.…”
Section: Discussionmentioning
confidence: 99%